Pengaruh Kepuasan Kerja Terhadap Hubungan Antara Independensi, Pengalaman, Due Professional Care Dan Akuntabilitas Dengan Kualitas Audit ( Studi Empiris Pada KAP di Surakarta & Yogyakarta ) - Kawastri, Kawastri; , Dr. Fatchan Ahayani, M.Si (2015)
The purpose of this study was to determine the effect of job satification on independence, due professional care, and accountability with audit quality in the publik accounting firm in Surakarta andYogyakarta. The date used in this study is primary date in the form of a respondent's answares from questionaire date collection. This study used a puposive sampling method in the determinastion of the sample and there were 34 samples that meet the criteria. This study used multiple linear regression analysis for the date analysis technique, in which the results shawed variable job satisfacation, independence, due professional care and accountability not effect on audit quality.